Considering musical style and genre (Orfeu, 2025)
‘Considering musical style and genre’ is an essay that combines two texts by Allan F. Moore published in different decades: “Categorical Conventions in Music Discourse: Style and Genre” (Music & Letters 82/3, 2001) and “Style and Genre as a Mode of Aesthetics” (Musurgia XXV/3, 2018). As well as offering the Portuguese-speaking reader a review of these two central concepts for music research, it is inspiring to observe the changes in the musicologist's perspective over time. In 2001, with a more ‘positivist’ attitude, in 2018 including issues of musical aesthetics, without forgetting to mention the recent 2024 communication, where the existence of a certain degree of subjectivity on the part of the musical analyst is admitted. It is important to emphasise the interaction between the translators and the author, since the proposal to publish the texts together prompted Moore to write a few paragraphs especially for this publication, in order to serve as a link between the first and second parts of the essay.